Investigation of knowledge, attitude and behaviors of university students on testicular cancer: results from two different cities - Yakar, Burkay; Pirincci, Edibe; Şen, Mehmet Ali; Genç, Ezgi (My University, 2023)
Objectives: Testicular tumors are the most common malign tumor in men aged 15-35 years. Early diagnosis and treatment is crucial in testicular cancer because if detected at an early stage, testicular cancer can be completely cured. Because of this reason increase in awareness and regular testicular self-examination (TSE) is recommended in the early diagnosis of testicular cancer. This study aimed to investigate the knowledge, attitude and behaviors of students about testicular cancer and testicular self-examination. Methods: This descriptive and cross-sectional study was conducted in Health care vocational schools of 2 different universities between November 2018 and January 2019. Data were obtained by a self-applied questionnaire comprised of four sections. Results: One hundred and six (37.7%) participants could not answer any question correctly. While 65.8% (n = 185) of the participants stated that they had heard of testicular cancer, the rate of those who heard about TSE was 17.8% (n = 50). Only 5.7% (n = 16) of the participants reported performing TSE. Binary logistic regression analysis was shown that the following factors increase men’s intention to perform TSE: Students’ academic unit [OR = 4.36, 95% CI: 1.37-13.88], age [OR = 0.2; 95% CI: 0.008-0.72], city [OR = 0.64; 95% CI: 1.15-1.49], those who have heard of TC before [OR = 0.71, 95% CI: 0.016-0.917], received information about TC [OR = 0.001, 95% CI: 0.015-0.309], and those who have heard of TSE before [OR = 0.01; 95% CI: 0.001-0.079]. Conclusions: One-third of the university students had never heard of testicular cancer, and TSE was not sufficiently practiced. There is a lack of information on this issue. It was thought that organizing training programs on the subject would raise awareness and save lives by early diagnosis.
Keywords: Knowledge; cancer screening; Testicular neoplasms; testicular cancer; testiculer self-examination; behaviours